Hyponatremia in Young Patients with Pulmonary Tuberculosis and Tuberculous Meningoencephalitis - Muhammad Iqbal Fanani; Komang Yunita Wiryaning Putri; Retna Dwi Puspitarini; Ali Santosa; Indah Kusuma Wardani (Faculty of Medicine, Universitas Jember, 2023)
Pulmonary tuberculosis (PTB) is an uncommon respiratory infection that rarely leads to the development of hyponatremia, a condition characterized by low levels of sodium in the blood. In most cases symptoms andiated hyponatremia are mild to moderate, often lacks noticeable symptoms, and can be effectively reversed through treatment with anti-TB medications. Hyponatremia is diagnosed when the serum sodium level falls below 135 mmol/L, and it is considered severe when the level drops below 125 mmol/L. Among electrolyte imbalances, hyponatremia is one of the most frequently observed, with a prevalence ranging from 1 to 4% in its severe manifestation. This journal reports the case of a male patient who presented with decreased consciousness, suspected to be associated with moderate hyponatremia, tuberculous meningoencephalitis, pulmonary tuberculosis, and sinus bradycardia. The patient's symptoms associated with hyponatremia were relatively mild, prompting the need for further evaluation to ascertain the root cause of the electrolyte imbalance. This is particularly important for patients with suspected tuberculosis who are also experiencing complications related to hyponatremia.